(untitled) (Research, Society and Development, 2025)
This case report aims to discuss the clinical presentation, diagnostic approach, and therapeutic management, comparing it with other reports documented in the literature. Acute Esophageal Necrosis (AEN), also known as "Black Esophagus," is a rare and severe condition characterized by diffuse necrosis of the esophageal mucosa, predominantly in the distal third. We report the case of a 67-year-old man, chronic alcoholic and severely malnourished, who presented with hematemesis and epigastric pain. Diagnosis was confirmed by upper endoscopy, which revealed dark and friable mucosa. Management included cessation of oral intake, clinical support with hydration, electrolyte replacement, vitamin supplementation, and broad-spectrum antibiotics. The patient showed progressive improvement, with signs of re-epithelialization after 10 days and hospital discharge after 25 days. This case is compared to other reports, highlighting risk factors, prognosis, and the importance of early diagnosis. The study contributes to understanding AEN and emphasizes the role of a multidisciplinary and individualized approach.